Synthesis of graphene oxide/reduced graphene oxide-silver nanocomposites for sensor application / An‘Amt Mohamed Noor - An ‘Amt, Mohamed Noor (2017)
Graphene, a single layer of sp2-bonded carbon atoms has recently become a huge interest that acts as a potential nanomaterial due to its advantages and unique sensory properties. The incorporation of metal nanoparticles on graphene as nanocomposite has been reported to significantly improved the material properties through surface modification. Hence, the development of the graphene-based nanocomposites has demonstrated excellent potential in the fabrication of highly sensitive sensors. A simple, cheaper, and reproducible technique to prepare graphene-based metal nanocomposites on a large volume is required in order to achieve successful incorporation of metal nanoparticles onto graphene-based materials. Therefore, a novel, easy to handle, less-toxicity, and high yield production of graphene oxide/graphene-based metal nanocomposites has been successfully designed. Herein, the synthesis and characterization have been reported, including the investigation on the relationship between the nanocomposite and the sensor performance. In this thesis, the first part focused on the synthesis of graphene oxide–silver (GO-Ag) nanocomposite which uses a simple ultrasonication irradiation method. The morphology revealed that the spherical Ag nanoparticles with an average size of ~ 12 nm were uniformly distributed on the GO layer. Both the spectral and colorimetric methods were performed on the optical detection of Hg2+ ions and the results showed that the limit of detection (LOD) achieved is 0.59 μM. The GO-Ag nanocomposite managed to exhibit good selectivity towards the detection of Hg2+ ions in the presence of higher concentration of other environmentally related heavy metal ions. In the electrochemical study, a catalytic current was displayed by the cyclic voltammogram in the reduction of H2O2 at the GO-Ag nanocomposite modified glassy carbon electrode (GCE). The nanocomposite modified electrode showed a linear range of 100 μM–11 mM (R2 =0.988) towards the detection of H2O2 by using amperometric i-t curve. The LOD was set to be 28.3 μM. On top of that, the v sensor was stable as the current responses were reproducible for the purpose of repeated measurements. The aim for the second part of the study was to synthesize GO-Ag as well as reduced graphene oxide – silver (rGO-Ag) nanocomposite by using microwave irradiation method for the spectrophotometric and surface enhanced raman spectroscopy (SERS) detection of dopamine (DA) including the electrochemical sensing of 4-Nitrophenol (4-NP). The average particle size was found to be ~20 nm, but the size of Ag nanoparticles can be tuned by adjusting the irradiation time. It was also observed that the GO-Ag nanocomposite exhibited good SERS activity on DA substrate with micromolar concentration. Apart from that, the spectrophotometric determination of DA was also studied by using nanocomposite while the response of AgNPs SPR band with the successive addition of DA was linearly increase in absorbance with the red shifting of wavelength of 100 nM to 2 μM concentration range. The LOD was found to be 66.1 nM in determining the DA. In the electrochemical study, the amperometric i-t has been used to detect the low concentration of 4-nitrophenol (4-NP). The rGO-Ag nanocomposites modified GCE was also observed to exhibit a notable electrochemical reduction towards 4-NP with a linear range of 1- 10 μM (R2 = 0.9985) and a detection limit of 0.32 μM. In summary, this work has successfully synthesized GO/rGO-Ag nanocomposites for highly sensitive optical and electrochemical sensor.